THE EFFECTS OF TAXATION KNOWLEDGE, THE EXPRESSION OF TAX SANCTIONS ON TAXPAYER COMPLIANCE - Andari, Diah (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine whether awareness of taxpayers and tax penalties affect taxpayer compliance at the Tegallega Tax Office. The factors tested in this study are awareness of taxpayers and taxation sanctions as independent variables. Tax compliance has been identified as the dependent variable. The research method used in this study is the explanatory method. The population in this study was all individual taxpayers registered at the Tegallega Primary Tax Service Office, with a total population of 129,394 people. The sampling technique used in this study is the probability sampling technique with a simple random sampling technique, as well as by using the Slovin formula. While the number of samples in this study amounted to 100 individual taxpayers. While the analytical method used in this study is multiple linear regression analysis at a significance level of 10%. The program used in analyzing data uses Statistical Package for Social Sciences (SPSS) Ver19.00. Based on the results of research, it partially and simultaneously shows that awareness of taxpayers and tax sanctions affect the compliance of taxpayers in the Tax Office Pratama Tegallega. The magnitude of the effect of awareness of taxpayers and tax sanctions in contributing influence to taxpayer compliance by 52.2%.